Pengaruh CR dan DER terhadap ROE pada Perusahaan Perdagangan Eceran di BEI Periode 2015-2018 - Amalia Tiara Balqish (Politeknik Ganesha Medan, 2020)
Phenomenon in this study lie in the average value of Return on Equity which tends to decline in 2015-2018. While the average value for the Current Ratio and Debt to Equity Ratio has a good value. When the average value of the Current Ratio is good, but the average value of Return On Equity can be said to be bad. This is the purpose of this research, to find out whether there is an effect of Current Ratio and Debt to Equity Ratio on Return On Equity in retail trade subsector companies listed on the Indonesia Stock Exchange period 2015-2018, both partially and simultaneously. This study uses a purposive sampling method in selecting samples from retail trade subsector companies listed on the Indonesia Stock Exchange for the period 2015-2018. This study also uses multiple linear regression analysis methods. The results showed that partially, Current Ratio had no effect on Return On Equity because it had a significance value greater than 0.05, and Debt to Equity Ratio had a significant effect on Return On Equity because it had a significance value of less than 0.05. While simultaneously, Current Ratio and Debt to Equity Ratio significantly influence Return On Equity.